Case Report: Immune reconstitution inflammatory syndrome after hematopoietic stem cell transplantation for severe combined immunodeficiency - Liu, Shuangjun; Huo, Feng; Dai, Guorui; Wu, Jie; Qin, Maoquan; Mao, Huawei; Wang, Quan (Frontiers in Immunology, 2022)
We report a case of immune reconstitution inflammatory syndrome（IRIS） after hematopoietic stem cell transplantation (HSCT). The patient had sever bacillus Calmette-Guerin(BCG)-vaccine caused disseminated infection and had received allogeneic HSCT for X-linked severe combined immunodeficiency disease(SCID). After HSCT, complicated by treatment-responding veno-occlusive disease(VOD) and acute graft-versus host disease(GvHD),at the time when immunosuppressants were withdrawn the patient experienced recurrent fever accompanied by elevated inflammatory indicators. After receiving glucocorticoids and ibuprofen, the patient's condition improved and a diagnosis with BCG related IRIS was made.